Recria de corderos merino en valles irrigados. Una alternativa de integración entre productores del secano y riego - Alvarez, Juan Mauricio; Garcia Vinent, Juan Carlos; Mayo, Ayelén; Roa, Martin Alejandro; Gallego, Juan Jose (EEA Valle Inferior, INTA, 2021)
EEA Valle Inferior